# Cofactor Sum Identity

## Theorem

Let $J_n$ be the $n \times n$ matrix of all ones.

Let $A$ be an $n \times n$ matrix.

Let $A_{ij}$ denote the cofactor of element $\tuple {i, j}$ in $\map \det A$, $1 \le i, j \le n$.

Then:

$\ds \map \det {A -J_n} = \map \det A - \sum_{i \mathop = 1}^n \sum_{j \mathop = 1}^n A_{ij}$

## Proof

Let $P_j$ equal matrix $A$ with column $j$ replaced by ones, $1\le j \le n$.

Then by the Expansion Theorem for Determinants applied to column $j$ of $P_j$:

$\ds \sum_{j \mathop = 1}^n \map \det {P_j} = \sum_{j \mathop = 1}^n \sum_{i \mathop = 1}^n A_{ij}$

To complete the proof it suffices to prove the equivalent identity:

$\ds \map \det {A -J_n} = \map \det A - \sum_{j \mathop = 1}^n \map \det {P_j}$

Expansion of left hand side $\map \det {A - J_n}$ for the $2 \times 2$ case illustrates how determinant theorems will be used:

 $\ds A$ $=$ $\ds \begin {pmatrix} a & b \\ c & d \end {pmatrix}$ where $A$ is an arbitrary $2 \times 2$ matrix $\ds J_2$ $=$ $\ds \begin {pmatrix} 1 & 1 \\ 1 & 1 \end {pmatrix}$ $J_2$ is the $2 \times 2$ ones matrix $\ds \map \det {A -J_2}$ $=$ $\ds \map \det {\begin {matrix} a - 1 & b - 1 \\ c - 1 & d - 1 \end {matrix} }$ matrix subtraction $\ds$ $=$ $\ds \map \det {\begin {matrix} a & b - 1 \\ c & d - 1 \end {matrix} } - \map \det {\begin {matrix} 1 & b - 1 \\ 1 & d - 1 \end {matrix} }$ Determinant as Sum of Determinants $\ds$ $=$ $\ds \map \det {\begin {matrix} a & b - 1 \\ c & d - 1 \end {matrix} } - \map \det {\begin {matrix} 1 & b \\ 1 & d \end {matrix} }$ Multiple of Row Added to Row of Determinant $\ds$ $=$ $\ds \map \det {\begin {matrix} a & b \\ c & d \end {matrix} } - \map \det {\begin {matrix} a & 1 \\ c & 1 \end {matrix} } - \map \det {\begin {matrix} 1 & b \\ 1 & d \end {matrix} }$ Determinant as Sum of Determinants $\ds$ $=$ $\ds \map \det A - \map \det {P_2} - \map \det {P_1}$ Definition of $P_1$ and $P_2$ $\ds$ $=$ $\ds \map \det A - \sum_{j \mathop = 1}^2 \map \det {P_j}$ equivalent identity verified for $n = 2$

Let $A$ be an $n \times n$ matrix.

Let matrix $Q_m$ equal ones matrix $J_n$ with zeros replacing all entries in columns $1$ to $m$.

For example, for $n = 5$ and $m = 2$:

$Q_2 = \begin {pmatrix} 0 & 0 & 1 & 1 & 1 \\ 0 & 0 & 1 & 1 & 1 \\ 0 & 0 & 1 & 1 & 1 \\ 0 & 0 & 1 & 1 & 1 \\ 0 & 0 & 1 & 1 & 1 \\ \end {pmatrix}$

Induction on $m$ will be applied to prove the induction identity:

$\ds \map \det {A - J_n} = \map \det {A - Q_m} - \sum_{j \mathop = 1}^m \map \det {P_j}$

for $1 \le m \le n$.

Induction step $m = 1$
 $\ds \map \det {A - J_n}$ $=$ $\ds \map \det {A - Q_1} - \map \det {P_1 - Q_1}$ $P_1$ equals $A$ with column $1$ all ones. $\ds \map \det {P_1 - Q_1}$ $=$ $\ds \map \det {P_1}$ Add ones in column 1 to columns $2 \cdots n$, $\ds \map \det {A - J_n}$ $=$ $\ds \map \det {A - Q_1} - \map \det {P_1}$ combining equations

Induction step $m = k$ and $k < n$ implies $m = k + 1$
 $\ds \map \det {A - J_n}$ $=$ $\ds \map \det {A - Q_k} - \sum_{j \mathop = 1}^k \map \det {P_j}$ Induction hypothesis $m = k$ $\ds \map \det {A - Q_k}$ $=$ $\ds \map \det {A - Q_{k + 1} } - \map \det {P_{k + 1} - Q_{k + 1} }$ Determinant as Sum of Determinants on column $k + 1$ $\ds \map \det {P_{k + 1} - Q_{k + 1} }$ $=$ $\ds \map \det {P_{k + 1} }$ Add ones in column $k + 1$ to columns $k + 2 \cdots n$ $\ds \map \det {A - J_n}$ $=$ $\ds \map \det {A - Q_{k + 1} } - \map \det {P_{k + 1} } - \sum_{j \mathop = 1}^k \map \det {P_j}$ combining preceding three equations $\ds \map \det {A - J_n}$ $=$ $\ds \map \det {A - Q_{k + 1} } - \sum_{j \mathop = 1}^{k + 1} \map \det {P_j}$ Induction completed.

Conclusion

Matrix $A-Q_n$ equals $A$ because $Q_n$ is the zero matrix.

Let $m = n$ in the induction identity, then:

$\ds \map \det {A - J_n} = \map \det A - \sum_{j \mathop = 1}^n \map \det {P_j}$

$\blacksquare$